Screen-printed and spray coated graphene-based RFID transponders. (21st November 2019) - Jaakkola, K; Ermolov, V; Karagiannidis, P G; Hodge, S A; Lombardi, L; Zhang, X; Grenman, R; Sandberg, H; Lombardo, A; Ferrari, A C
Abstract: We report ultra-high-frequency (UHF, 800 MHz–1 GHz) radio frequency identification (RFID) transponders consisting of printed dipole antennas combined with RFID microchips. These are fabricated on Kapton via screen printing and on paper via spray coating, using inks obtained via microfluidization of graphite. We introduce a hybrid antenna structure, where an Al loop (small compared to the overall size of the antenna) is connected to a microchip with the double function of matching the impedances of antenna and microchip and avoiding bonding between exfoliated graphite and chip. The transponders have reading distance  ̃11 m at UHF RFID frequencies, larger than previously reported for graphene-based RFID and comparable with commercial transponders based on metallic antennas.